Changes in modifiable risk factors for Alzheimer´s disease and dementia during the COVID‐19 pandemic in Swedish older adults: a population‐based digital survey. (20th December 2022) - Rocha, Ana Sabsil Lopez; Mangialasche, Francesca; Thunborg, Charlotta; Levak, Nicholas; Aspö, Malin; Rydström, Anders; Lehtisalo, Jenni; de Jager, Celeste A; Price, Geraint J; Hall, Anette; Solomon, Alina; Ngandu, Tiia; et al.
Abstract: Background: Older adults have a higher risk of Alzheimer´s disease (AD) and dementia. In terms of morbidity and mortality, they also represent the group most severely affected by the SARS‐CoV‐2 (COVID‐19) pandemic. Since February 2020, the Swedish government recommended different general measures limiting mobility and social contact, to contain the spread of infection. Pandemic‐related changes in lifestyle and access to healthcare could have a negative impact on modifiable factors for AD and dementia. Methods: A digital survey was distributed to the general population (multiple distribution channels, voluntary participation) during the last waves of the COVID‐19 pandemic in Sweden (May/2021 – December/2021). Participants were people aged 60+ years, free of dementia, and living in Sweden. The survey aimed to measure changes in lifestyle (e.g., diet, physical activity), care of vascular/metabolic risk factors (e.g., diabetes, hypertension), as well as psychosocial factors (e.g., depressive symptoms, sleep quality, social isolation) relevant for AD and dementia. The survey is part of the World‐Wide‐FINGERS‐SARS‐CoV‐2 initiative. Results: 6, 918 participants completed the survey, mean age was 67.9 (5.11 SD), 58% were female, 71.6% were from urban areas. Preliminary results showed that, during the pandemic, 27% of participants decreased their physical activity, 26.3% increased intake of unhealthy snacks, 25.7% experienced increased sleep problems. Also, 58.7% had less contact with family, 40.4% experienced loneliness, 24.7% experienced worsening of memory, and 26.8% rated their health worse than before the pandemic. On the other hand, the reported increase in consumption of vegetables and fruits was 14.1% and 15.7%, respectively, and 65.2% of people had increased the use of digital services to keep in contact with family and friends. Also, 2.6% of participants decreased smoking, and 11.2% reduced their alcohol consumption. The occurrence of chronic vascular and metabolic diseases and related disruption in access to healthcare is presented in Table 1. Conclusion: The COVID‐19 pandemic has had an effect on modifiable factors for AD and dementia in Swedish older adults. These changes can affect future AD/dementia occurrence and should be addressed in forthcoming interventions for AD/dementia risk reduction and prevention. The survey can also be used for pre‐screening participants for prevention trials.